Hemodynamic Effects of Methamphetamine and General Anesthesia - Keyvan M. Safdari; Curtis Converse; Fanglong Dong; Nickolas Alan MacDougall; Kevin Hyer; Alec Runyon; Haley Ahlering; Mark E. Comunale (Anesthesiology Research and Practice)
Study Objective. In our practice, we deal with a significant number of patients who require general anesthesia for elective or semielective surgeries and are positive for illicit methamphetamine. We sought to examine our clinical impression that these patients become hemodynamically unstable under general anesthesia. Design. A retrospective analysis of all anesthetic records at our institution over a two-year period was performed. Setting. Operating room cases under balanced anesthesia. Patients. All patients with ASA class I or II, who did not have trauma or were initially admitted to ICU, aged 18–65, without preexisting cardiac, renal, or pulmonary disease. Patients were divided into three groups: those acutely positive for methamphetamine within 48 hours of surgery (n = 137), those positive for methamphetamine between 48 hours and 7 days of surgery (n = 69), and randomly selected controls who were negative for methamphetamine within 7 days of surgery (n = 159). Measurements. Intraoperative hemodynamic instability was defined as either a drop of more than 40% in MAP for greater than 5 minutes or requirement for significant amount of vasopressors. Main Results. Among the patients who were acutely positive for methamphetamine within 24 hours, 31.4% met the criteria for hemodynamic instability within the first hour of general anesthesia, compared to 26.1% of the subacutely positive patients and 6.3% of controls (p<0.0001). This was despite lower doses of anesthetic medications in the acutely and subacutely positive groups. Conclusion. Patients who present to the operating room with a positive urine drug screen for amphetamines within 2 days of surgery are at increased risk of hemodynamic instability. Postponing surgery up to 7 days somewhat decreases this risk, but not to the levels of patients who do not use methamphetamines.